Analysis of Figurative Language In Poem’s Provide, Provide By Robert Frost - Muhammad Nur Khasan; Deddi Andrea Chofan (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This article analyzes figurative language in the poem Provide Proven by Robert Frost. Robert Frost is one of the writers who uses various types of figurative language in his work. The purpose of using figurative language in poetry is to emphasize the meaning of the author that he wants to express. Apart from that, it is also used to beautify the sound of poetry. Data was collected from text and analyzed using descriptive-qualitative research. The results of this research show that there are five types Figurative language: metaphor, irony, personification, alliteration.